Proton motive force toothbrush - Moran, Francis (2002)
The present invention is composed of a dry cell wafer battery circuit enclosed in the dielectric handle of a toothbrush. It has a photovoltaic cell with a rectifying diode used to revitalize the battery if necessary. The inventive system is used to obtund tooth decay and periodontal lesions by obstructing the Proton Motive Force that exists in bacteria. The result is that glycolysis, DNA synthesis, and chelation is upset and this will cause bacteria to dissolute logarithmically. The inventive system is also used to harden and remineralize enamel and dentin by using fluoride compounds available in over the counter dental cleansers. Regular use of these products depends on passive and random action of fluoride and bicarbonate molecules existing in dentifrice, gels, and rinses in a slurry condition in saliva. These are subject to buffers of bicarbonate and phosphate ions of the saliva and are not very efficient. The system of invention takes into consideration the vector magnitude of the water layer between the enamel and the pellicle plaque layer of teeth which insulates the teeth from the electrical potentials of electrophoresis. The claim that electrical potentials can be placed on teeth does not take this physico-chemical phenomena into consideration. This invention will use the proper voltage to produce ionization of molecules in a salivary slurry of gels, dentifrice's, and rinses.